Kesejahteraan Spiritualitas Dapat Meningkatkan Kualitas Hidup Pasien Kanker - Agustina Rifa; Dewi Gayatri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the spiritual well-being of improving the quality of life of cancer patients. The method used is Literature Review using the ClinicalKey Nursing database, SAGE Journal, and ScienceDirect. The research results show that of the 620 articles found, there are 15 articles selected based on the title and abstract. Papers were read in total, and 12 articles were selected according to the criteria. The study results show that spiritual well-being can improve the quality of life of cancer patients. In conclusion, fulfilling the spiritual well-being needs of cancer patients will have an impact on improving the quality of life of cancer patients related to reducing the effect on symptoms of physical and psychological conditions and increasing social relations during the treatment and treatment process. Keywords: Cancer, Spiritual Welfare, Quality of Life